HGG-23. DRUG SCREENING LINKED TO MOLECULAR PROFILING IDENTIFIES NOVEL DEPENDENCIES IN PATIENT-DERIVED PRIMARY CULTURES OF PAEDIATRIC HIGH GRADE GLIOMA AND DIPG. Issue 2 (22nd June 2018) - Mackay, Alan; Molinari, Valeria; Carvalho, Diana; Pemberton, Helen; Temelso, Sara; Burford, Anna; Clarke, Matthew; Fofana, Mariama; Boult, Jessica; Izquierdo, Elisa; Taylor, Kathryn; Bjerke, Lynn; et al.
Abstract: Paediatric high grade glioma and diffuse midline glioma (including DIPG) are comprised of multiple biological and clinical subgroups, the majority of which urgently require novel therapies. Patient-derived in vitro primary cell cultures represent potentially useful tools for mechanistic and preclinical investigation based upon their retention of key features of tumour subgroups under experimental conditions amenable to high-throughput approaches. We established 21 novel primary cultures derived from patients in London, Dublin and Rome, and together with cultures shared from Barcelona, Brisbane and Stanford we assembled a panel of 42 models under 2D (laminin matrix) and/or 3D (neurospheres) conditions, fully credentialed by phenotypic and molecular comparison to the original tumour sample (methylation BeadArray, panel/exome sequencing, RNAseq). Screening against a panel of 400 approved chemotherapeutics and small molecules, we identified specific dependencies associated with tumour subgroups and/or specific molecular markers. Examples included cells with sensitizing (HSJD-GBM-001, PDGFRA_A385ins; HSJD-DIPG-008, PDGFRA_D846N) or resistance (HSJD-GBM-002, PDGFRA_D842Y) mutations to a range of PDGFRA inhibitors, and individual models showing profound sensitivity to multiple FGFR (QCTB-R006) or EGFR (HSJD-DIPG-012) inhibitors. H3.3G34R cells were differentially sensitive to agents targeting the proteasome, whilst H3.3 K27M cells were responsive to crizotinib. MAPK-dysregulated PXA-like cultures differentially responded to inhibitors of upstream signalling via PKC and CK2. In total, 85% cells were found to have at least one drug screening hit in short term assays linked to the underlying biology of the patient's tumour, providing a rational approach for individualised clinical translation.